A cross selectional survey in a critical care: the job satisfaction and functioning team of the health professionals - La Sala, Rachele; Boninsegni, Katiuscia; Tani, Alice; Rasi, Alice; Sansovini, Linda; Scarpelli, Giulia; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2016)
Background and Aim of the work: Health care workers, especially those who are part of the OS core, are essential in the delivery of services, as they represent the institution at the time of the contact with the user and they represent also the image of the organization. Health administrations, therefore, are called to improve the performance through a better motivation and satisfaction of the staff, in view of two strategic aspects: job satisfaction of professionals and team collaboration. Method: Between January and September 2014, a survey at the OU (UUOO) intensive care and sub intensive has been made inside three hospitals in Emilia Romagna. It’ s been a multicentre cross-sectional quantitative study by administering a self-report questionnaire designed to investigate the different constructs. On 742 questionnaires were spread 454 professionals gave it back  (response rate = 73%). Of those, 273 (60.1%) were nurses, 119 (26.2%) were physicians and 62 (13.7%) were healthcare operators. 62 (13.7%) Job Satisfaction was measured with the McCloskey Mueller Satisfaction Scale. Team Functioning was measured with the Index of Interprofessional Team Collaboration. Results: Results from MANOVA indicated that physicians were less satisfied of scheduling than both nurses and healthcare operators. For professional opportunities, instead, healthcare operators showed the lower level of satisfaction. The participants seem to perceive a high level of team effectiveness and therefore the professionals involved in the care of critically ill patients than the two dimensions analysed, (reflection between the processes and interdependent roles), also state a greater tendency to respect the roles interdisciplinary, maintaining their professional autonomy and a lower tendency to use critical thinking to act professionally in order to improve the effectiveness of care provided. Conclusion: The study results oriented healthcare administrators, to take paths that feed the job satisfaction and the collaboration of professionals by developing the aspects investigated. Considering the shared perception among the professions studied, compared to the constructs under investigation, it seems to be clear how the routes should be designed in a systematic order to involve, in an integrated way the best professionals (nurses, doctors and OSS) involved in taking managing critical patients. No statistically significant difference have been found between these three professions considered, on most dimensions of job satisfaction investigated (relations between colleagues, ‘social interactions, work-family balance, time work organization and working professional opportunity). There is a difference between two specific factors: the work time planning organization and wich is seen less by the nurses, while the job opportunities that are perceived less from the OOS.